Shelf Life and Quality Evaluation of Deep Frozen Coconut Cream, Coconut Scrapings and Coconut Slices - Arachchi, L. A. C. N. Lihinikadu; Gunathilake, K. D. P. P.; Prasadi, V. P. N. (International Coconut Community, 2016)
Coconut kernel is the major energy source in the diets of coconut producing countries. Ready to use coconut milk/kernel has a great demand in the market specifically for its nutty flavor. Studies were conducted to evaluate the storage quality of deep frozen coconut cream, scraped coconut and coconut slices. Coconut cream pasteurized and scraped coconut and coconut slices were blanched at 70 °C for 1.5 minutes. A known weight of each product was packed in nylon low density polyethylene, triple laminate and polyethylene and stored in a freezer at -18 °C. The shelf life was evaluated by free fatty acid content (FFA), peroxide value (PV) and total microbial load. The acceptability was tested using a triangle test with a 25 semi trained panelists in two weeks intervals for two months. FFA content increased during the storage period, but none of the products exceed the standard level of 1% The development of FFA in products packed in triple laminates was slow and peroxides were not detected up to 8 weeks of storage period. At the 8th week, microbial count reached to 106. Sensory study revealed that the organoleptic properties of all three coconut products were within the acceptable range though products showed differences sometimes, after 4 weeks storage compared with fresh samples. The results indicated that the minimum shelf life of the frozen coconut products is 8 weeks.